1988
DOI: 10.1002/jsfa.2740450108
|View full text |Cite
|
Sign up to set email alerts
|

Myosin thermal stability in fish muscle

Abstract: The thermal stability of fish muscle proteins varies between species with considerable implications for storage and processing properties. Myosins were isolated jiom cod and snapper, cold-and tropical-water fish respectively, and their thermal melting characteristics were compared using differential scanning calorimetry over a range of pH and ionic strength conditions. At pH 6 and ionic strength 0.06 M , cod myosin exhibited a thermal melting transition 10 K lower than snapper myosin, reflecting a comparable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 15 publications
5
22
0
Order By: Relevance
“…In addition, the results would also indicate that the native muscle has higher thermal stability than the isolated myofibrillar proteins. These results agree with those reported by other authors (1,28,29). In addition, the results shown in Figures 1, 2, and 3 would indicate that the paramyosin content does not have a direct influence on the thermal stability of proteins.…”
Section: Thermal Behavior Of Both Striated and Smooth Wholesupporting
confidence: 95%
“…In addition, the results would also indicate that the native muscle has higher thermal stability than the isolated myofibrillar proteins. These results agree with those reported by other authors (1,28,29). In addition, the results shown in Figures 1, 2, and 3 would indicate that the paramyosin content does not have a direct influence on the thermal stability of proteins.…”
Section: Thermal Behavior Of Both Striated and Smooth Wholesupporting
confidence: 95%
“…Under such increasingly exacting conditions, the myosins of tropical fish appear to be disrupted similarly to the otherwise less stable cold-water fish. Davies et al (1988) observed a similar effect for isolated red snapper (tropical) myosin compared to cod (cold-water) myosin. They suggested that differences in the aggregation characteristics of fish myosins may partly explain their different thermal denaturation properties in vitro.…”
Section: Discussionsupporting
confidence: 70%
“…2 Amongst ®sh species, myosin from cold-water ®sh is more sensitive to changes in the physicochemical environment than myosin from warm-water ®sh. 3 Fish muscle proteins, especially myosin, show an optimal thermal gelation around pH 6.0. 3±6 As the pH increases above this value, the transition temperature of myosin decreases, 5 and this is associated with protein destabilisation and consequently a lower gelforming ability.…”
Section: Introductionmentioning
confidence: 99%